Inhibition Of JNK Phosphorylation By Curcumin Analog C66 Protects LPS-Induced Acute Lung Injury - Xiao Z; Xu F; Zhu X; Bai B; Guo L; Liang G; Shan X; Zhang Y; Zhao Y; Zhang B (Dove Medical Press, 2019)
Zhongxiang Xiao,1,2 Fengli Xu,3 Xiaona Zhu,1 Bin Bai,1 Lu Guo,4 Guang Liang,1 Xiaoou Shan,3 Yali Zhang,2 Yunjie Zhao,2 Bing Zhang1,2 1Affiliated Yueqing Hospital, Wenzhou Medical University, Wenzhou, Zhejiang 325600, People’s Republic of China; 2Chemical Biology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3Department of Pediatrics, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang 325000, People’s Republic of China; 4Department of Pharmacy, The First People’s Hospital of Huzhou, Huzhou, Zhejiang 313000, People’s Republic of ChinaCorrespondence: Bing ZhangAffiliated Yueqing Hospital, Wenzhou Medical University, Wenzhou, Zhejiang 325600, People’s Republic of ChinaTel +86-577-61575506Email zhangbing197102@163.com Yunjie ZhaoChemical Biology Research Center, School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou 325035, People’s Republic of ChinaTel +86-577-86699892Email aabye1100@aliyun.comBackground: Acute lung injury (ALI) is characterized by high prevalence and high mortality. Thus far, no effective pharmacological treatment has been made for ALI in clinics. Inflammation is critical to the development of ALI. Curcumin analog C66, having reported as an inhibitor of c-Jun N-terminal kinase (JNK), exhibits anti-inflammatory property both in vitro and in vivo. However, whether C66 is capable of reducing lipopolysaccharide (LPS)-induced ALI through the inhibition of inflammation by targeting JNK remains unknown.Methods: Intratracheal injection of LPS was employed to build a mouse ALI model. H&E staining, wet/dry ratio, immunofluorescence staining, inflammatory cell detection, and inflammatory gene expression were used to evaluate lung injury and lung inflammation. In vitro, LPS was used to induce the expression of inflammatory cytokines both in protein and gene levels.Results: The results of our studies showed that the pretreatment with C66 and JNK inhibitor SP600125 was capable of attenuating the LPS-induced ALI by detecting pulmonary edema, pathological changes, total protein concentration, and inflammatory cell number in bronchoalveolar lavage fluid (BALF). Besides, C66 and SP600125 also suppressed LPS-induced inflammatory cytokine expression in BALF, serum, and lung tissue. In vitro, LPS-induced production of TNF-α and IL-6 and gene expression of TNF-α, IL-6, IL-1β, and COX-2 could be inhibited by the pretreatment with C66 and SP600125. It was found that C66 and SP600125 could inhibit LPS-induced phosphorylation of JNK both in vitro and in vivo.Conclusion: In brief, our results suggested that C66 protects LPS-induced ALI through the inhibition of inflammation by targeting the JNK pathway. These findings further confirmed the pivotal role of JNK in ALI and implied that C66 is likely to serve as a potential therapeutic agent for ALI.Keywords: acute lung injury, lipopolysaccharide, JNK, C66, inflammation